Countering Radicalism, Promoting Peace: Insights from Pesantren Al-Anwar 3 Sarang Rembang, Central Java - Muhammad Asif; Abdul Najib; M. Ridlwan Hambali; Faridlatus Sya’adah (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2021)
As a religious institution, pesantren is expected to be able to spread Islamic values of raḥmatan li al-‘ālamīn and counter radicalism in Indonesia. The portrait of such a pesantren is, for example, reflected in Pesantren Al-Anwar 3 Sarang. This study aims to reveal the efforts made by Pesantren Al-Anwar 3 Sarang in countering radicalism and terrorism in the country. It is a field study with a qualitative approach, where the data were obtained through participatory observation, in-depth interviews, and document analysis. This study found that Pesantren Al-Anwar 3 Sarang had initiated serious efforts in order to counter radicalism. First, the pesantren teaches the values of diversity to students so that they may act more wisely in responding to differences in cultures, thoughts, and religious ideologies. Second, the pesantren instills in students that the Unitary State of the Republic of Indonesia (NKRI) has been in accordance with Islamic law and the best form of compromise as the embodiment of Dawlah Mu‘aḥidīn (a treaty-based state). Third, the pesantren opposes radical ideologies which are believed to be one of the crucial factors in the birth of violent acts. Fourth, the pesantren propagates tolerance and pluralism because both are believed to be sourced from the teachings of Islam and the Qur'an. Fifth, the pesantren promotes Islamic moderation. Lastly, the pesantren calls for peace among mankind. Overall, the efforts made by Pesantren Al-Anwar 3 Sarang are expected to be a reference for other pesantren in countering radicalism.